Rabies and rabies problems in Nigeria - Ogunkoya, A. B.; Osinubi, M. O.V.; Garba, A.; Audu, S. W.; Atuman, Y. J.; Ehimiyein, A. M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Official reporting of rabies in Nigeria started in 1912. The National Veterinary Research Institute (NVRI), Vom, within the last 77 years, confirmed 4809 cases of animal rabies in Nigeria. Rabies control through immunization programs has crashed woefully and consequently, the rabies situation has become chaotic and confounding. Locally, only 2,137,615 doses of dog anti-rabies vaccines were produced between 1956 and 2005 (average 43,625 per year) by NVRI, Vom. Dog population in Nigeria is currently estimated at 8 million. In the last 20 years of research and follow ups on rabies and associated problems, only 10% of the dogs’ population received anti-rabies immunization. Within the immunized dogs, rabies outbreaks occurred frequently. Evidences on the trend of rabies cases recorded (1983-1991) confirmed 40%-60% increase in rabies positive cases for every decade in Nigeria. Molecular epidemiology and phylogenetic analysis study of some dog rabies isolates in Plateau State confirmed the flow of rabies virus from neighboring and far North African countries into Nigeria. Some studies of prevalence of rabies antigens in the brain and saliva of apparently healthy dogs slaughtered for human consumption in Nigeria; revealed a 28% prevalence of rabies antigen in the consumed dogs in North-West, 31% from North-East and 24% from North-Central regions of Nigeria. Similarly, 6%-8% of the dogs had rabies antigen in their saliva at the point of slaughter. A study of the epidemiology of rabies in wildlife in Bauchi State, revealed the presence of rabies antigen in mongoose (11%), jackals (9%), squirrels (8.3%), hydrax (17%) and wild cats (16%). This suggests an ongoing spread of rabies within the wild animals in Nigeria. Conclusively, rabies is a problem in Nigeria such that even the apparently healthy dogs slaughtered for human consumption harbor the viral antigen in the brains and saliva. This is an obvious public health risk and may have serious implication. The low number of Nigerian dogs immunized (10% instead of 70-80%) leaves the country with abundance of epizootic siblings for rabies outbreaks. The wide spread of rabies in the wildlife is an emerging proof of the role of wildlife in the epidemiology of rabies in Nigeria. It is our recommendation that a RITA model to rabies control as employed in the Americas be applied in West Africa especially Nigeria.